2019
DOI: 10.4018/ijthi.2019010102
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Information Security Behaviours of Tanzanian Government Employees

Abstract: This article investigates security behaviours of employees using the Health Belief Model (HBM) as a theoretical lens. Given the fact that previous studies on security behaviours paid much attention to conscious information security behaviours; this article extends the HBM to study both habitual or automatic security behaviours (security habit) and conscious security behaviours of Tanzanian government employees. A structural equation modelling (SEM) technique was used for data analysis. The study found that, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…For Hypothesis 1 (H1), as illustrated in Table 6 and Figure 6, the result of this study is highly supported the perceived benefits are positively related to privacy and personal data protection behavior in MCC (b = 0.315, SE = 0.56, p = 0.000). The current result is now lead to the same findings of the previous work by Ng et al [15], Claar et al [49], Humaidi et al [19,50], Williams et al [20], and Koloseni et al [51] that the perceived benefits are positively related to behavior [15,19,20,[49][50][51].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…For Hypothesis 1 (H1), as illustrated in Table 6 and Figure 6, the result of this study is highly supported the perceived benefits are positively related to privacy and personal data protection behavior in MCC (b = 0.315, SE = 0.56, p = 0.000). The current result is now lead to the same findings of the previous work by Ng et al [15], Claar et al [49], Humaidi et al [19,50], Williams et al [20], and Koloseni et al [51] that the perceived benefits are positively related to behavior [15,19,20,[49][50][51].…”
Section: Discussionsupporting
confidence: 87%
“…For Hypothesis 6 (H6), as demonstrated in a group of previous studies by Ng et al [15], Humaidi et al [19], and Koloseni et al [51], and Williams et al [20], the perceived severity is positively related to behavior [15,19,20,51]. The outcome of this study, as shown in Table 6, supported that perceived severity related to privacy and personal data protection behavior in MCC through perceived threat (b = 0.60, SE = 0.025, p = 0.007).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations